Patient autonomy and education in specific medical knowledge - Daniel Lukas (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2010)
The asymmetry between the patient as a layman and the physician as an expert is a key element in health economics. However, a change to a higher degree of patient autonomy has taken place. Furthermore, there is a consensus in a positive correlation between general education and productivity of medical care. This paper focuses on the individual investments of laymen in specific medical education as a decision problem in which the ex-post strategies of the individual are consultation and self-care as imperfect substitutes. It is assumed that specific knowledge increases the self-diagnosis competence (self-protection) and the self-care productivity (self-insurance) as dimensions of autonomy. The analysis is divided into two forms of ex-post decision making according to individual rationality: 1. ambiguity 2. uncertainty. An elaboration of necessary conditions for investments in education is undertaken.
Keywords: D01; D80; I12; I20; 330; patient autonomy; education; self-care; ambiguity; uncertainty